2018
DOI: 10.1111/jan.13765
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality is associated with nocturnal glycaemic variability and fear of hypoglycaemia in adults with type 1 diabetes

Abstract: These findings suggest that glycaemic control and FOH are targets for intervention to improve sleep quality in those with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 48 publications
7
49
2
4
Order By: Relevance
“…Glycaemic fluctuations increase the risk of hypoglycaemia, regardless of the treatment used, including oral hypoglycaemic agents and insulin . Night‐time glycaemic fluctuations are also known to affect the quality of sleep, indicating that prevention of such fluctuations may lead to improved sleep quality and quality of life for patients with diabetes. We found that the addition of canagliflozin to insulin improved the night‐time glycaemic fluctuations, suggesting its beneficial effects on hypoglycaemia and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Glycaemic fluctuations increase the risk of hypoglycaemia, regardless of the treatment used, including oral hypoglycaemic agents and insulin . Night‐time glycaemic fluctuations are also known to affect the quality of sleep, indicating that prevention of such fluctuations may lead to improved sleep quality and quality of life for patients with diabetes. We found that the addition of canagliflozin to insulin improved the night‐time glycaemic fluctuations, suggesting its beneficial effects on hypoglycaemia and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, almost 80% of adults with type 1 diabetes believed waking in the night had a negative impact on their usual daily functioning, including mood and happiness, family relationships, work and the ability to exercise regularly and eat healthily . Suboptimal subjective sleep quality has been related to higher levels of daytime sleepiness, fatigue, symptoms of depression and anxiety, and diabetes‐specific distress in adults with type 1 or type 2 diabetes and higher worries about hypoglycaemia in adults with type 1 diabetes . Furthermore, increases in sleep quality have been associated with fewer next‐day diabetes‐specific and general stressors in adults with type 1 diabetes .…”
Section: Overview Of Findings In the Past 25 Yearsmentioning
confidence: 99%
“…rapid declines . Also, higher glycaemic variability (represented by the standard deviation of measured levels) has been related to higher sleep latency and lower subjective sleep quality and duration .…”
Section: Overview Of Findings In the Past 25 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with 48 T1DM patients [ 5 ] measured sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and poor sleep quality was reported by 46% of patients. Similarly, a systematic review and meta-analysis studies using validated questionnaires have shown that T1DM patients with lower HbA1c levels reported good sleep quality, while patients with poor sleep quality have higher HbA1c levels [ 6 ].…”
mentioning
confidence: 99%